A flexible liquid‐metal alloy bandpass filter. Issue 5 (10th February 2018) - Li, Rongqiang; Guo, Yong‐Xin; Chen, Wei; Li, Yida; Voon‐Yew Thean, Aaron
Abstract: This article presents a liquid‐metal Galinstan alloy bandpass filter (BPF) with good flexibility, which is fabricated by an improved soft lithography process. The Galinstan alloy is enclosed in the microfluidic channels of elastomeric polydimethylsiloxane (PDMS) substrates. Together with the PDMS substrates, the Galinstan alloy based filter features bending, twisting and stretching capabilities along any direction. A second‐order open‐loop resonator filter with 2.4 GHz center frequency and 15% fractional bandwidth was designed and fabricated to verify this concept. Experiments show that frequency response of the filter is almost unaffected in the case of bending of the different radii or twisting, while its center frequency slightly shifts down in the stretching condition. The proposed filter can be used for the flexible and conformal electronics.